Relato integrado e valor de mercado de companhias brasileiras - Santos, Cassius Klay Silva (2022)
The disclosure model called Integrated Reporting (IR) comes up with a proposal to present financial and non-financial information in a single report format, with emphasis on six types of capital (Human, Intellectual, Manufactured, Social and Relationship, Natural and Financial), as proposed by the IIRC (2013). Different studies have evaluated that the disclosure of information in the IR model contributes to the information content disclosed by companies and has the potential to contribute to the market value of companies. However, no research was identified that assesses the context of voluntary disclosure of this information, or that directly verifies the type of content disclosed in RI. Therefore, the main objective of this research was to identify the relationship between the information disclosed in the integrated report prepared based on IIRC guidelines and the market value of Brazilian companies. To meet the objective, it was necessary to work in three stages: 1. Develop a compliance instrument for disclosing company information in the IR model, theoretically validated; 2. Identify when the stock market reacts in relation to the IR disclosure; 3. Analyze how the information associated with IR impacts on the formation of the Market Value of companies listed on B3. The research sample consisted of 54 companies listed on B3, with IR disclosure over the years 2017, 2018, and 2019. The development of this research resulted in the construction of an IR compliance instrument, theoretically validated with the application of the IR Delphi technique. It was also identified that in the first disclosure of the IR, by the companies listed on B3, there was a lower-thanexpected effect on the second post-disclosure day, evaluated by the event study. Finally, even having identified a correlation between the types of capital and the market value of the companies, it was not found, for the investigated sample, an effect of disclosure of information on the six types of capital, which make up the IR model, in the value of companies in the multilevel regression analysis process. These findings suggest that the information in the IR model affects the share price after disclosure, and can be a reference base for users' decision making. The results also advocate the potential that the information in the IR structure has in relation to the definition of the market value of companies, in a context of voluntary disclosure. However, no statistically positive contribution was observed in the content disclosed in the RI model and the market value of the companies.